Research on the Practical Path of High-quality Urban Development from the Perspective of New Development Concept- Reflections on the Phenomenon of "Zibo Barbecue" - Tu, Duoyang (International Journal of Social Sciences and Public Administration, 2024)
High-quality development is the Party and the state for the new development stage of economic and social construction of the goal of a high degree of summary, is related to the fundamental well-being of the people and promote the process of socialist modernization of the important task. The new vision of innovative, coordinated, green, open and shared development is an important thought guiding China’s economic and social development in the new era, and it also points out the only way to achieve higher-quality development. At present, there are still constraints in the process of promoting high-quality development in cities. This paper takes the phenomenon of "Zibo Barbecue" as a case study from the perspective of new development concepts, explores its practical reasoning, and summarizes successful experience in order to provide reference for other cities to promote high-quality development.